Climate Change and its Impacts across Pakistan: Climate Change and its Impacts across Pakistan - Sarfaraz, Sardar; Faisal, Nadeem (International Journal of Economic and Environmental Geology, 2023)
Climate change and variability is best manifested by persistent global temperature rise, changing precipitation patterns, increasing frequency of extreme weather events, rapidly shrinking ice sheets & glacier melting and sea-level rise. This study analyzed the rainfall (for three major seasons; monsoon, winter & spring), temperature (in three indices; annual mean, annual daytime and annual nighttime temperatures) and extreme events recorded at 56 data sites across Pakistan over 63-years period (1961-2023) to investigate the climate change and diagnose the trends. We did time-series analysis to assess the annual variability and applied the Mann-Kendall statistical trend test to determine the trend’s significance. Results showed a significant rise in annual-average temperature, annual maximum as well as annual minimum temperatures all over Pakistan and at 27 stations individually, annual maximum temperature at 28 and annual minimum at 25 stations across Pakistan. In rainfall, the annual and spring (AMJ) rains have shown significant rising trend throughout Pakistan, while, the summer monsoon (JAS) rainfall showed a statistically significant increase at 8 stations in the north with decrease at 2 sites in southwest, winter (DJFM) rainfall witnessed an increase at 3 sites and so was the spring (AMJ) at 7 sites mostly in the south, while a decrease at 3 sites in north of the country (all changes being significant at 95- 99% CI). Extreme events include an increase in annual high-temperature extreme (Tmax > 35 °C), decrease in annual cool nights (Tmin < 10 °C) and increase in wet days. The snowfall has decreased in both amount and frequency of snow days in KP, GB and Punjab hilly station, Murree. There is an increasing frequency of cyclone formation in the Arabian Sea, particularly the intensity being significant. Sea-level data analysis depicted a 2.02 mm/year sea-level rise at Karachi coast. Increased cyclones frequency coupled with potentially heightened storm surges and sea-level rise may prove fatal to coastal areas. Keywords; Climate change, extreme weather events, rainfall, temperature, sea-level rise, tropical cyclone.